2013
DOI: 10.4049/jimmunol.1301378
|View full text |Cite
|
Sign up to set email alerts
|

Human Memory Helios− FOXP3+ Regulatory T Cells (Tregs) Encompass Induced Tregs That Express Aiolos and Respond to IL-1β by Downregulating Their Suppressor Functions

Abstract: FOXP3+ regulatory T cells (Tregs) are critical regulators of self-tolerance and immune homeostasis. In mice and humans, two subsets of FOXP3+ Tregs have been defined based on their differential expression of Helios, a transcription factor of the Ikaros family. Whereas the origin, specificity, and differential function of the two subsets are as yet a source of controversy, their characterization thus far has been limited by the absence of surface markers to distinguish them. In this article, we show that human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
72
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(93 citation statements)
references
References 33 publications
19
72
2
Order By: Relevance
“…1b). This finding was consistent with previous reports [14][15][16][17]. Both subsets highly expressed CTLA4, CCR4 and contained approximately 12 % Ki67 + cells, indicating that the two T cell subsets were activated in vivo (Fig.…”
Section: Resultssupporting
confidence: 93%
“…1b). This finding was consistent with previous reports [14][15][16][17]. Both subsets highly expressed CTLA4, CCR4 and contained approximately 12 % Ki67 + cells, indicating that the two T cell subsets were activated in vivo (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Helios, a transcription factor belonging to the Ikaros family, has been studied extensively in the context of human T reg in health and disease [14,[16][17][18][19][20]36]. We have a longstanding interest in the rheumatic joint, a site of inflammation characterized by extensive cell influx and proliferation and where, in addition to activated memory effector T cells, T regs are also enriched significantly compared to PB [23].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a recent study demonstrated that the chemokine receptor CCR7 in combination with the cytokine receptor IL-1R1 was restricted largely to the Helios-negative subpopulation of FoxP3 1 T cells [20]. Hence, we analysed if these markers could also be applied to Helios Fig.…”
Section: Il-1r1 Expression Is Elevated Significantly On Both Helios 1mentioning
confidence: 99%
See 1 more Smart Citation
“…28 Conversely, IL-17 and Helios expression tended to be mutually exclusive (Fig. 5F, left), according to the intrinsic stability of Helios high Tregs 1,16,29 and to the segregation between Helios and RORgt expression in gut Tregs. 30 OX40 expression was similarly distributed in IL-17-positive and -negative cells (Fig.…”
Section: Il-17-producing Tconvs and Tregs Accumulate At Tumor Site Anmentioning
confidence: 97%